Toward sustainable output generation of liquid–solid contact triboelectric nanogenerators: The role of hierarchical structures. (February 2019) - Cho, Handong; Chung, Jihoon; Shin, Gunsub; Sim, Jae-Yoon; Kim, Dong Sung; Lee, Sangmin; Hwang, Woonbong
Abstract: Nanogenerators harvesting energy from triboelectrification between liquid and solid are gaining remarkable interest as a new energy conversion method. To ensure complete detachment of liquid from the surface, superhydrophobic surfaces have been considered as an attractive material. The hierarchy of the structure of superhydrophobic surfaces is important for retention of the superior wetting properties, but the effects of the hierarchical structures on the energy harvesting performance of triboelectric nanogenerators have only been rarely examined. We first report the significance of the hierarchical structure on durable and stable output generation of superhydrophobic triboelectric nanogenerators. In addition, we show that the hierarchical structure makes it possible to generate electricity even from a liquid with low surface tension and high viscosity. Based on these findings, we suggest a practical sensor application that can easily and quickly measure the concentration of liquids such as ethylene glycol. Graphical abstract: Highlights: Hierarchical structures utilized for sustainable liquid-solid contact TENGs. Relationship between electrical output and behavior of impact droplets on surfaces. Generating electricity from low surface tension and high viscosity liquids.